Step Into a New Dimension of the Android App Development World for Beginners - Azima, Fauzan; Memanda, Freddy; Habibie, Muhammad Fadhil; Qardhawi, Nadif Yusuf; Gimnastiar, Nazar; Mujiastuti, Rully; Sutrisno, Mirza; Meilina, Popy; Nurbaya Ambo, Sitti; Adharani, Yana (Society : Jurnal Pengabdian Masyarakat, 2025)
Technological developments in the field of mobile applications have opened up many opportunities in various sectors. However, beginners often face obstacles due to a lack of basic knowledge about Android app development, so it is important for them to get a comprehensive and easy-to-understand education. In this context, the author and team organised an event titled “Step Into A New Dimension Of The Android App Development World For Beginners” with the aim of introducing the basics of Android app development to beginners with a structured approach. The programme was implemented through Webinars and Workshops, which included exposure to basic concepts to hands-on practice in creating simple applications. The evaluation results showed a positive response from 62 participants who came from various backgrounds, with 68% expressing satisfaction and 32% very satisfied with the implementation of this activity. In addition, the Pre-Test and Post-Test results showed an increase in participants' understanding of Android application development. This activity succeeded in providing a strong foundation for beginners to enter the world of Android application development.